The effect of humour usage on customer’s service experiences - Chiew, Tung Moi; Christine Mathies; Paul Patterson (2018)
Cross-disciplinary research recognises humour as an effective communication tool for fostering engagement and positive interpersonal relationships, although inappropriate use can create negative outcomes. Drawing on positive psychology, this study aims to empirically examine the extent to which frontline employee’s (FLE’s) humour usage can influence customers’ service encounter evaluations. Findings from 252 retail service customers indicate that their sense of humour drives humour perceptions and facilitates positive encounter evaluations. In particular, FLEs’ other-directed humour, rather than self-directed humour, leads to more enjoyable interactions for customers. This effect is moderated by pre-encounter mood, in that customers react more positively to other-directed humour when they are in a bad mood. This study contributes empirical support for the importance of appropriate humour usage to the service encounter literature. From a managerial perspective, the outcomes highlight that service encounters benefit from other-directed humour.